민간약 신경초의 생약학적 연구 - 배지영(Ji Yeong Bae); 구영민(Young Min Goo); 박종희(Jong Hee Park); 안미정(Mi Jeong Ahn) (생약학회지, 2013)
A Korean folk medicine, "SinKyungCho" has been used to cure common cold and rheumatis. While this crude drug has similar morphological feature to that of Rubia species, the botanical origin has never been studied pharmacognostically. Therefore, in order to clarify the botanical origin of "SinKyungCho", the morphological and anatomical characteristics of Rubia species growing in Korea, i.e. R. akane, R. chinensis var. glabrescens, R. cordifolia var. pratensis, R. cordifolia var. sylvatica were studied. Especially, differing from the other three species, R. cordifolia var. pratensis has 2-4 cork cell layers under the endodermal cell layer. R. cordifolia var. sylvatica showed the largest number of parenchyma cell layers in cortex by 8-17. While the average ratio of stele to root transverse section is over 45% for R. akane and R. cordifolia var. pratensis, the ratio is under 45% for R. chinensis var. glabrescens and R. cordifolia var. sylvatica. According to these morphological criteria, the folk medicine "SinKyungCho" from Korean traditional market was proved to be the underground part of R. akane.